A review of the environmental and health impact of biotechnology applications in sustainable aquaculture and fish health management - Ojewole, Akinloye Emmanuel; Badmus, Omolola; Ndimele, Prince Emeka; Toromade, Adekunle Stephen; Akande, Olufemi Stephen; Ojewole, Catherine Oluwalopeye (Frontiers in Aquaculture, 2026)
Aquaculture provides over half of global aquatic animal production for human consumption and is vital to food security, yet intensification increases disease susceptibility, causing significant losses annually. This study examines biotechnology applications for sustainable aquaculture and fish health, evaluating their performance and implications. It also discusses disease drivers in aquaculture, pathogen groups (bacterial, viral, parasitic, fungal), alongside control measures. Advances include probiotics, vaccines, phage therapy, molecular diagnostics, selective breeding, and emerging tools like nanotherapeutics and CRISPR/Cas9. Probiotics and vaccines can reduce antibiotic use and improve resistance, but outcomes depend on strain, host, dose, and environment, limited by standardization and safety concerns. Antibiotic use remains widespread, contributing to antimicrobial resistance and food safety risks, including severe toxicities. Genetic interventions enhance disease resistance but face pathogen-specific limitations and ecological risks. Responsible implementation requires improved stewardship, wastewater treatment, containment strategies, harmonized governance, and ethical frameworks integrating precision aquaculture to achieve sustainable production while protecting ecosystems and public health.